Private information, human capital, and optimal 'home bias' in financial markets - Isaac Ehrlich; Jong Kook Shin; Yong Yin (Institute for the Study of Labor (IZA), 2011)
By allowing for imperfectly informed markets and the role of private information, we offer new insights about observed deviations of portfolio concentrations in domestic relative to foreign risky assets, or home bias, from what standard finance models predict. Our model ascribes the bias to endogenous information acquisition bolstered by investors' human capital. We develop discriminating hypotheses about the influence of specific and general human capital endowments and direct and opportunity costs of managing risky assets in determining whether to hold these assets, and how the assets' portfolio shares vary across investors and financial markets. These hypotheses are supported by numerical and econometric analyses of panel data from the US over 1992-2007, and 23 international financial markets over 2001-2007. The results indicate the existence of differences across countries in the degree to which home asset prices are information-revealing, which may be relevant for fully understanding the global financial crisis of 2007-09.
urn:nbn:de:101:1-201111072746
Keywords: D82; F30; G11; G12; G15; J24; 330; private information; human capital; home bias; financial markets; risky assets; global financial crisis; Portfolio-Management; Home Bias Puzzle; Asymmetrische Information; Internationaler Finanzmarkt; USA; Welt